The Clash Of Property And Environmental Rights In The Niger Delta Region Of Nigeria - Lugard, Sunday Bontur (Journal of Sustainable Development Law and Policy, 2025)
The Niger Delta region of Nigeria, home to about 30 million people, is one of the world’s most prominent deltas. Petroleum exploration in this region has been ongoing for over fifty years and revenue from this activity is at present the mainstay of the Nigerian economy. Granted that it is impracticable to undertake petroleum operations without some negative impact on the environment, a good deal of this pollution can be mitigated. The International Oil Companies (IOCs) are complacent about pollution reduction to a sustainable level; regulatory agencies are either compromised or lack the required expertise or equipment to monitor and enforce compliance with extant environmental protection laws and regulations. The pursuit of the IOCs’ property right over petroleum resources has set them against the other stakeholders’ right to a healthy environment. The clash of these rights can best be addressed by ascribing “collective property” and not “private property” right to the acreage over which they have been granted licence to prospect for, explore or mine petroleum resources.